Analisis perbedaan: Penerapan model pembelajaran berbasis masalah terintegrasi scaffolding - Yusnidar; M. Dwi Wiwik Ernawati; Dwi Agus Kurniawan; Miftahul Zannah Azzahra; Fhadira Insani Putri; Rahmat Perdana (Postgraduate, University of Mataram, 2023)
The purpose of this research is to find out how students' creative thinking skills use the usual Problem Based Learning model with an integrated scaffolding problem-based learning model. This study uses a quantitative method with a comparative type. The sample used was 42 class X students from each school, bringing the total to 168 students. The sampling technique used is random sampling. In this study using quantitative data analysis with SPSS 26, to look for descriptive statistics and inferential statistics. Based on the analysis that has been done, it can be concluded that there are differences in students' creative thinking skills using the problem-based learning model and students' creative thinking abilities using the integrated scaffolding problem-based learning model in the four schools.